Perancangan Jaringan MAN Dengan Dyamic Routing EIGRP Dan Algoritma DUAL Menggunakan Cisco Packet Tracer - Falih Nawwaf; Moch. Hari Purwidiantoro; Lilik Sugiarto (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
Metropolitan Area Network (MAN) is a computer network that covers a geographical area larger than LAN (Local Area Network) but smaller than WAN (Wide Area Network). In the design of MAN networks is very important because it ensures the availability, reliability, and efficiency of routes to transmit data throughout the network. Therefore, the use of dynamic routing protocols such as the Enhanced Interior Gateway Routing Protocol (EIFRP) with the Diffusing Update Algorithm (DUAL) algorithm and simulated on Cisco packet tracer is the main concern in this study.